The portrait : a novel [large type] - Steel, Danielle (Random House Large Print Publishing, 2025)
"Devon Darcy's reputation precedes her. As a highly sought-after portrait artist, she seems to have the ability to peer into the souls of her subjects and then capture them on canvas. But the world doesn't know about the devastating losses she has endured, first as an orphan, then as a far-too-young widow. When entrepreneur Charles Mackenzie Taylor sees her at a New York gallery event, he is instantly haunted by her beauty and her talent. Having lost his mother when he was thirteen, and still living in the cold shadow of his late banker father's disapproval, Charlie has given up on love. He's resigned himself to a loveless marriage to avoid the inconvenience of divorce. But Devon awakens something in him across that crowded gallery, and she is in turn intrigued by Charlie. He approaches her to paint his portrait, and while her schedule is booked for many months before she can accommodate him, with the electricity between them palpable."--